2020
DOI: 10.3389/fonc.2020.01682
|View full text |Cite|
|
Sign up to set email alerts
|

Mucinous Adenocarcinoma of the Rectum: A Whole Genome Sequencing Study

Abstract: Introduction: Mucinous adenocarcinoma of the rectum is an infrequently encountered histological subtype that is associated with an impaired response to chemoradiotherapy and a worse overall prognosis. A genomic profile analysis of mucinous rectal tumors has not yet been performed. The aim of this study was to comprehensively describe the burden of somatic mutations and copy number variation as well as perform mutational signature and microbial analysis of an in-house collected cohort of mucinous adenocarcinoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 62 publications
0
7
1
Order By: Relevance
“…Thirdly, alterations in the fundamental genes of the MAPK pathway and high microsatellite instability (MSI) status were more likely to be associated with MCA. 1,28 However, we did not detect RAS and BRAF mutations or MSI status. Thus, we did not determine the relationship between molecular features and FPR, as well as their predicted efficacies.…”
Section: Discussioncontrasting
confidence: 60%
“…Thirdly, alterations in the fundamental genes of the MAPK pathway and high microsatellite instability (MSI) status were more likely to be associated with MCA. 1,28 However, we did not detect RAS and BRAF mutations or MSI status. Thus, we did not determine the relationship between molecular features and FPR, as well as their predicted efficacies.…”
Section: Discussioncontrasting
confidence: 60%
“…A recent publication by our group, premised on the hypothesis that the impact of F .nucleatum/Fusobacteriales may differ according to underlying tumour biology, demonstrated a correlation between increased Fusobacterium prevalence and poor prognosis in mesenchymal type tumours only (11). A previous whole genome sequencing study, again undertaken by our group; examined 10 mucinous rectal adenocarcinomas, and found F. nucleatum to be signi cantly overrepresented within mucinous tumour tissue (20). F. nucleatum has previously been shown to promote MUC2, TNF-α and mucin production in colonic cells (21).…”
Section: Introductionmentioning
confidence: 71%
“…To verify the validity of the antisera, sections from 8 tumours which had previously undergone whole genome sequencing, were stained with the antisera. Fusobacterium burden was quanti ed and levels were compared with Fusobacterium relative abundance as interpreted previously from existing sequencing data (20).…”
Section: Pan-fusobacterium Outer Membrane Antiseramentioning
confidence: 99%
“…Over 100 epidemiological studies have been identified in the primary search specifically mentioning F. nucleatum in the abstract. Supplementary Table 10 summarizes the characteristics and main outcomes of 42 of these epidemiological studies which met the eligibility criteria, most of which comparing F. nucleatum presence/abundance in feces from CRC patients versus healthy controls and of tumor tissue versus adjacent normal tissue ( Supplementary Table 10 ; Castellarin et al, 2012 ; Flanagan et al, 2014 ; Fukugaiti et al, 2015 ; Ito et al, 2015 ; Mira-Pascual et al, 2015 ; Wang et al, 2016 ; Xie and Fang, 2016 ; Yu et al, 2016 , 2017 ; Amitay et al, 2017 ; Drewes et al, 2017 ; Eklöf et al, 2017 ; Liang et al, 2017 , 2021 ; Scott et al, 2017 ; Suehiro et al, 2017 ; Yamamura et al, 2017 ; Yoon et al, 2017 ; Hale et al, 2018 ; Hsieh et al, 2018 ; Kwong et al, 2018 ; Repass, 2018 ; Russo et al, 2018 ; Tsuchiya et al, 2018 ; Bundgaard-Nielsen et al, 2019 ; Butt et al, 2019 ; Chen et al, 2019 ; De Carvalho et al, 2019 ; Kageyama et al, 2019 ; Saito et al, 2019 ; Tunsjø et al, 2019 ; Yachida et al, 2019 ; Zhang et al, 2019 ; Alkharaan et al, 2020 ; Boehm et al, 2020 ; Gantuya et al, 2020 ; Kashani et al, 2020 ; Reynolds et al, 2020 ; Eisele et al, 2021 ; Kawasaki et al, 2021 ; Kurt and Yumuk, 2021 ; Pignatelli et al, 2021 ). Two meta-analyses published in 2020 reported pooled ORs of 8.3 for detection of F. nucleatum in colorectal specimens (feces/mucosa/tissue) and being diagnosed with CRC, and 10.06 for detection of F. nucleatum in CRC tissue versus healthy tissue from controls ( Supplementary Table 7 ; Gethi...…”
Section: Resultsmentioning
confidence: 99%